Resistance and Ungendering: Poetry of Mona Zote and Monalisa Changkija - Biswas D.; Pramanik P. (My University, 2025)
While the academic world talks of different waves of feminism that have emerged in Europe and the US in the past few centuries, the feminists from the third world countries have reservations on the use of a western framework of feminism in investigating the challenges faced by the women from third world countries. The structural discrimination that permeates the gender divide in India is so variegated that a homogenous reprisal will be inadequate to understand the problems that persist among several ethnic communities in a postcolonial context. Neither religion nor education could erase the structural discrimination that continues to exist in these ethnic societies because of the persistence of regressive “customary laws” that allow male domination. This essay argues that the emerging feminist voices like Monalisa Chankija and Mona Zote from India's north-east have used “performativity” as a tool to counter these gendered societies on one hand, and on the other hand it has also un-gendered the “essence” of cultural constructs putting it under suspension. However, the success of this effort seems limited only to the literary world as efforts are still underway to bring substantial changes into the political world. © 2022 Aesthetics Media Services. All rights reserved.